Assessing the influence of urban geometry on noise propagation by using the sky view factor. Issue 3 (23rd February 2018) - Silva, L.T.; Fonseca, F.; Rodrigues, D.; Campos, A.
Abstract : The impact of traffic noise can be prevented by suitable planning measures. This study analyses the relationship between urban geometry and traffic noise, recognizing that the arrangement of buildings and streets greatly influences urban noise. The study was carried out in Braga, a medium-sized Portuguese city, by selecting locations with different urban geometries. At each site, the equivalent continuous sound level was measured. Furthermore, the urban geometry was evaluated by using the sky view factor, a parameter which shows the degree of sky obstructed by buildings. Results show an inverse proportionality between noise and the sky view factor. The highest noise levels were found in areas with a low sky view factor. The results also indicate that the sky view factor is a parameter which can potentially be used in research on urban noise.